PENGARUH KEBIJAKAN MONETER TERHADAP INFLASI DI INDONESIA (STUDI KASUS PRIODE TAHUN 2008 – 2013) - Misbahuddin Misbahuddin (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2016)
The purpose of this study was to analyze the influence of the BI rate set by Bank Indonesia, the narrow money supply M1 and M2 broad money supply on the inflation rate in Indonesia. Thus, it is also intended to answer the question